ENERGY AUDIT OF LIGHTING SYSTEM, AIR CONDITIONING SYSTEM AND MEDICAL EQUIPMENT IN YARSI PONTIANAK GENERAL HOSPITAL - Salim Nur Rohman, Raka Hafieda; Abidin, Zainal; Arsyad, M.Iqbal (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2023)
The energy audit at Yarsi Pontianak General Hospital aims to achieve efficient use of electrical energy without affecting the function and usefulness of a system. The audit method used is a detailed energy audit conducted on lighting systems, air conditioning, and medical equipment. The results of the research on Energy Saving Opportunities (PHE) obtained include PHE No Cost by reducing the ignition time and number of lights in the lighting system, reducing the ignition time and number of air conditioners in the air system, reducing the ignition time of medical equipment, at PHE Low Cost by installing infrared sensors and light sensors, changing the type of refrigerant to musicool refrigerant type, and at PHE High Cost by changing the type of lamp to LED, changing the AC unit to an energy-saving inverter air conditioner, and changing the type of medical equipment with low power consumption. The initial IKE value before doing PHE was 204.56 kWh/m2/year at a cost of Rp.553,541,364, after PHE No Cost the IKE value became 151.94 kWh/m2/year, after PHE Low Cost became 168.48 kWh/m2/year, and after PHE High Cost became 174.92 kWh/ /year. The savings obtained at PHE No Cost amounted to Rp.142,387,308, at PHE Low Cost amounted to Rp.97,636,797, and at PHE High Cost amounted to Rp.80,190,648.